Answer:
f(g(x)) =
![\sqrt{8x \: - \: 13} \: + \: 9](https://tex.z-dn.net/?f=%20%5Csqrt%7B8x%20%5C%3A%20%20-%20%20%5C%3A%2013%7D%20%20%5C%3A%20%20%2B%20%20%5C%3A%209)
Step-by-step explanation:
f(x) =
![\sqrt{x} \: + \: 9](https://tex.z-dn.net/?f=%20%5Csqrt%7Bx%7D%20%20%5C%3A%20%20%2B%20%20%5C%3A%209)
g(x) = 8x - 13
f(g(x) =
![\sqrt{8x \: - 13} \: + \: 9](https://tex.z-dn.net/?f=%20%5Csqrt%7B8x%20%5C%3A%20%20-%2013%7D%20%20%5C%3A%20%20%2B%20%20%5C%3A%209)
Ordering laptops. Much more expensive. Higher consequences.
it is a linear equation
if you take the negative of x and subtract 1 you get Y
so the answer is A
3x²-y³ - y³ - z if x = 3, y = -2, z = -5
Simply plug in all the values :)
3(3²) - (-2³) - (-2³) - (-5)
Simplify.
3(9) + 2³ + 2³ + 5
Simplify.
27 + 8 + 8 + 5
Simplify.
35 + 13
Simplify.
48
~Hope I helped!~